Farmer perception of utilization of rice ransplanterin Aceh Besar. Issue 1 (April 2020) - Mardhiah, Ainal; Khumaira,; Azis, Abdul; Basri, A.; Bakar,; Panikkai, S.
Abstract: During the last two years, agricultural mechanization technology has been very widely introduced to farmers in Aceh to increase agricultural production, especially rice. One of the mechanizations that were introduced to farmers as an alternative solution to overcome the limited planting labour is the Rice Transplanter. The purpose of this study was to determine the level of farmers' perceptions of the use of Rice Transplanter technology in Indrapuri District, Aceh Besar District. This research uses the case study method in the research location. The sampling technique was intentionally "Proposive Sampling" with the consideration that the population in this study had used a rice transplanter machine, with a population of 20 farmers scattered in two villages, Aneuk Glee and Lam Ilei. Data obtained in the form of primary data through interviews with respondents and secondary data as supporting data. Furthermore, the data were analyzed using descriptive analysis using a Likert scale. The linkert scale used is divided into 3 levels: 1 (low), 2 (medium), and 3 (high). The results showed that the total perception score of farmers who used a rice transplanter machine was 809 and was at the perception index of 82.2% which was included in the high category. This means that with the presence of a rice transplanter machine, farmers can save on the use of production costs at every harvest season, in addition to the level of appropriateness of the use of machinery on this paddy field also meets the criteria so that it is easy to traverse and plant rice seeds. Farmers' perception of the use of Rice Transplanter machines in IndrapuriSubdistrict is high because in terms of profits it is better than the manual method (using sickle), so it is evident that the production costs incurred are lower than in conventional systems.